2011
DOI: 10.1021/cs200430r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pt3Sn Alloy Nanoparticles and Their Catalysis for Electro-Oxidation of CO and Methanol

Abstract: A lloying a non-noble metal (M) with Pt has become a popular approach to Pt-based catalysts with much reduced Pt usage and enhanced Pt activity. 1À7 Depending on the chemical nature of M, PtM can be made highly active for either electrochemical oxidation or reduction. 5À8 Among various PtM alloys studied thus far, PtSn alloys represent an interesting group of catalysts not only for hydrogenation 9À11 and dehydrogenation reactions, 12À14 but also for electro-oxidation of carbon monoxide (CO), 15À20 methanol, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 35 publications
1
57
0
3
Order By: Relevance
“…Figure 4b shows the CO oxidation peaks. The literature affirms that Pt-Sn interactions weaken CO adsorption on Pt and promote the dissociation of the water to form Sn-OH ad near Pt-CO ad , facilitating faster CO oxidation [38,39]. The active area of the materials was estimated by integrating the area below the peaks, with the values presented in Table 1.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Figure 4b shows the CO oxidation peaks. The literature affirms that Pt-Sn interactions weaken CO adsorption on Pt and promote the dissociation of the water to form Sn-OH ad near Pt-CO ad , facilitating faster CO oxidation [38,39]. The active area of the materials was estimated by integrating the area below the peaks, with the values presented in Table 1.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…For example, Pt 3 Sn NPs are synthesized through the solutionbased hot-injection and co-reduction of Pt(acac) 2 and Sn(acac) 2 with the size tuned from 4 to 7 nm by controlling injection temperature [61]. For example, Pt 3 Sn NPs are synthesized through the solutionbased hot-injection and co-reduction of Pt(acac) 2 and Sn(acac) 2 with the size tuned from 4 to 7 nm by controlling injection temperature [61].…”
Section: Pt-based Np Catalysts For Mor and Faormentioning
confidence: 99%
“…Pt alloys such as PtePd, 40,41 PteRu, 40,42 PteAu, 20,43e45 PteCo, 26,46e49 PteCr and PteNi, 14,50 PteTi, 51 PteMn, 48 PteFe, 47,48,52 and PteSn, 53 and so on demonstrated some improved catalytic ORR activity when compared to pure Pt because of the synergistic role of the transition metals. It was reported that the catalytic activity of Pt 3 M (M ¼ V, Ti, Co, Fe, Ni) could be significantly improved with strong resistance to poisonous substances.…”
Section: Pt-alloying Strategymentioning
confidence: 99%